Предмет: Алгебра,
автор: Nastena2935
a) x^+x-6 б) 2x^-x-3 помогите пожалуйста разложить на множители
Ответы
Автор ответа:
0
х^2 + х - 6 = х^2 +3х-2х-6 =х(х+3)-2(х+3) = (х-2)(х+3)
2х^2 - х - 3 = 2х^2 + 2х - 3х - 3 = 2х(х+1) - 3(х+1) = 2х-3)(х+1)
2х^2 - х - 3 = 2х^2 + 2х - 3х - 3 = 2х(х+1) - 3(х+1) = 2х-3)(х+1)
Похожие вопросы
Предмет: Математика,
автор: 3ivanovdanil3
Предмет: Другие предметы,
автор: pmihail220
Предмет: Русский язык,
автор: Аноним
Предмет: Геометрия,
автор: Dashayakuba
Предмет: Математика,
автор: elenaanyfrieva